2018
DOI: 10.1002/psc.3143
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected dimerization of a tripeptide comprising a β,γ‐diamino acid

Abstract: Funding information China Scholarship CouncilWe have previously reported the synthesis of enantiopure β,γ-diamino acids and relevant short α/γ-peptide containing such building blocks. Complete nuclear magnetic resonance (NMR) studies, together with molecular modeling, highlighted the ability of a β,γ-diamino acid to induce various intramolecular turns. In this paper, we describe for the first time the formation of a dimeric structure constituted by α/γ/ α-tripeptide and stabilized by intermolecular interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Peptide design . Recently, one of our studies showed that β,γ‐DiAAs are capable of promoting dimerization when incorporated into α/γ‐hybrid tripeptides through extra hydrogen bonds [44] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide design . Recently, one of our studies showed that β,γ‐DiAAs are capable of promoting dimerization when incorporated into α/γ‐hybrid tripeptides through extra hydrogen bonds [44] …”
Section: Resultsmentioning
confidence: 99%
“…Recently, one of our studies showed that β,γ-DiAAs are capable of promoting dimerization when incorporated into α/γ-hybrid tripeptides through extra hydrogen bonds. [44] We thereby questioned whether these short peptides could serve as β-strand mimics in cyclopeptides. Inspired by the GS sequence, we employed the β-turn inducer ' D Phe-Pro' to constrain the dimeric tripeptide at both ends ( Figure 2).…”
Section: Peptide Design and Synthesismentioning
confidence: 99%
“…These findings are reminiscent of our previous results that instead of intra-molecular interaction, inter-molecular H-bonds are formed when (βR,γR)-DiAA 3 is introduced into short peptides. [45] As can be found in Table 2, the 3 J CαH-NH coupling constants of the Leu, Orn and Val (ranging between 8.6 and 9.1 Hz) of GS corresponds to a β-sheet structure. [46] A set of comparable values were calculated in GS6 while not in other analogues, signifying an analogous secondary structure between GS6 and GS.…”
Section: Introductionmentioning
confidence: 91%